Psychological and psycho-physical training as a part of physical education of students in higher educational establishments - Pichurin, V.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to analyze the phenomenon of psychological and psycho-physical training as part of physical education of students. Material: literary sources about problem investigation. Results: are given and analyzed a number of factors that determine the need for higher education in the special psychological and psycho-physical preparation for professional work. The question of psychological and psycho-physical preparation of students for professional work in the structure of physical education has considered. The difference has shown in the proposed concept of "psychological and psycho-physical training" known in physical education concept of "professionally applied physical training" and "psycho-physical preparation". Psychological and psycho-physical readiness is considered in the work as a kind of substructure overall personality structure. A model of psychological and psycho-physical preparedness of the student has proposed in this work. Conclusions: psychological and psycho-physical preparation of students for professional work can be done in physical education. It should be considered as part of physical education students in relation to specialized psychological and psychophysical characteristics of future careers.